METHODOLOGY FOR THE DEVELOPMENT OF TECHNICAL AND TACTICAL MOBILITY OF HIGHLY QUALIFIED BELT WRESTLERS - Mirzayev Abdulhamid Marifovich (Research Focus International Scientific Journal, 2023)
this article presents quite scientific innovations on the methodology of the development of technical and tactical mobility of highly qualified wrestlers in the training process.